Rotary ultrasonic machining of titanium alloy: effects of machining variables - Churi, N. J.; Pei, Zhijian J.; Treadwell, C. (My University, 2007)
Titanium and its alloys are finding prime applications in industries due to their unique properties. However, high cost of machining is one of the limiting factors for their widespread use. Tremendous efforts are being made to improve the existing machining processes and new processes are being developed to reduce the machining cost in order to increase the titanium market. However, there is no report on the systematic study of the effects of machining variables on output parameters in rotary ultrasonic machining of titanium and its alloys. This paper presents as experimental study on rotary ultrasonic machining of a titanium alloy. The cutting force, material removal rate, and surface roughness when rotary ultrasonic machining of a titanium alloy have been investigated using different machining variables.
Keywords: Cutting force; Drilling; Grinding; Material removal rate; Rotary ultrasonic machining; Surface roughness; Titanium alloy